2020
DOI: 10.3389/fphys.2020.609335
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustive Exercise and Post-exercise Protein Plus Carbohydrate Supplementation Affect Plasma and Urine Concentrations of Sulfur Amino Acids, the Ratio of Methionine to Homocysteine and Glutathione in Elite Male Cyclists

Abstract: Plasma and tissue sulfur amino acid (SAA) availability are crucial for intracellular methylation reactions and cellular antioxidant defense, which are important processes during exercise and in recovery. In this randomized, controlled crossover trial among eight elite male cyclists, we explored the effect of exhaustive exercise and post-exercise supplementation with carbohydrates and protein (CHO+PROT) vs. carbohydrates (CHO) on plasma and urine SAAs, a potential new marker of methylation capacity (methionine/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
3
5
0
Order By: Relevance
“…As small sample size limits statistical power, the results in our study might be considered as preliminary. However, our study size was comparable to those in some biochemical sports trials [64,65] and, as indicated by the interindividual differences in Figures 3-6, 8 and 9, increased s/uMHPG and u5-HIAA levels and improved Stroop performance were observed in EC participants, suggesting that the changes in central norepinephrinergic-serotonergic systems and attention performance were caused by the rhythmic rope jumping exercise. Moreover, while the effects of longrope jumping have been demonstrated, it is still unclear which aspect of the exercise is effective.…”
Section: Discussionsupporting
confidence: 81%
“…As small sample size limits statistical power, the results in our study might be considered as preliminary. However, our study size was comparable to those in some biochemical sports trials [64,65] and, as indicated by the interindividual differences in Figures 3-6, 8 and 9, increased s/uMHPG and u5-HIAA levels and improved Stroop performance were observed in EC participants, suggesting that the changes in central norepinephrinergic-serotonergic systems and attention performance were caused by the rhythmic rope jumping exercise. Moreover, while the effects of longrope jumping have been demonstrated, it is still unclear which aspect of the exercise is effective.…”
Section: Discussionsupporting
confidence: 81%
“…LYS is the precursor for carnitine [ 58 ] which transports fatty acids to the mitochondria, where they can be oxidised to produce acetil-CoA, involved in tricarboxylic acid (TCA) cycle [ 59 ]. Finally, for this group, according to data obtained by other authors [ 60 ], MET decreased after prolonged physical activity. This reduction may reflect increased transmethylation in which DNA, histones and other macromolecules are methylated in response to exercise [ 60 ].…”
Section: Discussionsupporting
confidence: 66%
“…Finally, for this group, according to data obtained by other authors [ 60 ], MET decreased after prolonged physical activity. This reduction may reflect increased transmethylation in which DNA, histones and other macromolecules are methylated in response to exercise [ 60 ]. PRO may also be related to the free fatty acids (FFA) release because some authors found a correlation between the decrease in PRO and the increase in FFA [ 25 ] as energy source during prolonged physical activity.…”
Section: Discussionsupporting
confidence: 66%
“…In contrast, PA has acute [ 171 ] and long-term effects on plasma concentrations of SAA [ 168 ]. We recently demonstrated that a 12-week combined endurance and strength exercise intervention led to marked changes in plasma SAA profiles of sedentary men [ 168 ], with reductions in plasma tCys, which otherwise has proven difficult to attain by dietary intervention in humans.…”
Section: Effects Of Long-term Pa On Irmentioning
confidence: 99%